ORANG JAWA DI SELANGOR - Mohammad Maiwan (Jurnal Ilmiah Mimbar Demokrasi, 2011)
This research aims to understand the forms of identity, culture and traditions of Javanese descent community in Kampung Semarang, Dengkil, Selangor, Malaysia. The method used is descriptive with qualitative approach. The research showed that the various traditions or social organization that originates from Javanese culture, for the most part, still practiced by the local community. In the context of Malaysia’s plural society, Javanese subculture, especially in Kampung Semarang, has a substantial contribution in enriching the national culture of Malaysia. In reality, the development process that takes place rapidly has significant impact to the community in perpetuate their cultural identity.